TRANSFORMATION OF ISLAMIC JURISPRUDENCE LEARNING THROUGH A LOVE B ASED LEARNING MODEL IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM AT MTS AN NAJAH TEBUIRENG 3 RIAU - Ani Rakhmawati; Hanifudin; Khoirotul Idawati (Program Studi Manajemen Pendidikan Islam, 2026)
This study aims to critically examine the transformation of Islamic Fiqh learning through the implementation of a love-based learning model within the Merdeka Curriculum framework, specifically the shift from a cognitive-normative approach to student-centered learning, oriented towards pedagogical relationships, and emphasizing the internalization of values and character building. This study uses a qualitative approach with a case study type conducted at MTs An Najah Tebuireng 3 Riau. Data collection techniques include in-depth interviews, learning observations, and documentation studies involving Islamic Fiqh teachers, students, and madrasah leaders. The results of the study indicate that; 1) The implementation of the Merdeka Curriculum at MTs An Najah Tebuireng 3 Riau encourages the transformation of Islamic Fiqh learning from a normative and student-centered approach to humanistic, contextual, and student-oriented learning. 2) The love-based learning model is systematically integrated into Islamic Fiqh learning through value-based planning, dialogic learning practices, an emotionally safe classroom climate, and holistic evaluation that emphasizes student development. 3) The integration of the Independent Curriculum and the love-based learning model results in a comprehensive transformation of Islamic Fiqh learning across various paradigms, pedagogical practices, educational relationships, and evaluation systems, and is effective in strengthening students' religious character